Depression Among College Students Due to the COVID-19 Pandemic - Hasanah, Uswatun; Fitri, Nuri Luthfiatil; Supardi, Supardi; PH, Livana (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Depression among college students is very common. College students are special groups that are in transition from adolescence to adulthood that can create stress in one's life. College students try to fit in, make plans for the future, and being away from home often causes anxiety and results in depression for college students. In addition, during the Covid-19 pandemic, students felt bored at home, did not understand material optimally, were confused with online learning methods, and felt their abilities and grades dropped dramatically. This study aims to determine the level of student depression during the Covid-19 pandemic. The quantitative research with a descriptive analytic approach. The research sample was 147 students, the study was conducted in May 2020 on the students of Akper Dharma Wacana. The research instrument used the BDI II questionnaire. Data were analyzed univariately with a frequency distribution. The results showed that 21.1% of students had mild depression, 17% of students had moderate depression and 3.4% had severe depression.